Determinants Of Investment Decisions Through Sharia P2P Lending Platforms By Lender’s Perspective - Dewi Diah Fakhriyyah; Heri Pratikto; Ludi Wishnu Wardana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The increasing popularity of financial technology, especially P2P lending as an alternative financing for business actors and SMEs, can provide investment options for potential investors to also provide financing for business actors. An investor/or provider of funding for business actors will decide to fund a project based on project information quality, return perception and trust. The aim of this research is to determine the influence of project information quality, return perception and trust on the investment decision of lender. The population of this research is members of chat group who had taken part in the fintech sharia webinar which was organized by the Indonesian Sharia Fintech Association. The sampling technique is purposive sampling with the criteria is individuals who have provided funding through the sharia P2P lending platform, and sample size determined by slovin formula. The result is each of project information quality, return perception, and trust positively affect investment decision. This reseach have a contribution to Theory of Planned Behavior which shows that investment decision as an attitude toward behavior influence by subjective norms (project information quality and trust) and perceived behavioral control (return perception).